2016
DOI: 10.1016/j.bbrc.2016.10.090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of induced Na+/Ca2+ exchanger overexpression on the spatial distribution of L-type Ca2+ channels and junctophilin-2 in pressure-overloaded hearts

Abstract: The Na/Ca exchanger 1 (NCX1) is an essential Ca efflux system in cardiomyocytes. Although NCX1 is distributed throughout the sarcolemma, a subpopulation of NCX1 is localized to transverse (T)-tubules. There is growing evidence that T-tubule disorganization is a causal event that shifts the transition from hypertrophy to heart failure (HF). However, the detailed molecular mechanisms have not been clarified. Previously, we showed that induced NCX1 expression in pressure-overloaded hearts attenuates defective exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Reynolds et al [54] found junctophilin-2 (JP-2) to be necessary for t-tubule maturation during mouse heart development and the defects of JP-2 can lead to t-tubule remodeling in ventricular myocytes [55]. A recent study suggested that NCX was causally linked to the spatial localization of JP-2 and organization of t-tubules in pressure-overloaded hearts [56], possibly due to abnormal JP-2 proteolysis through Ca-mediated calpain activation as previously described [57,58]. Whether the loss of TATs is a concomitant phenomenon of cellular remodeling or a direct consequence from the intracellular Ca elevation due to the absence of NCX in the KO cells remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al [54] found junctophilin-2 (JP-2) to be necessary for t-tubule maturation during mouse heart development and the defects of JP-2 can lead to t-tubule remodeling in ventricular myocytes [55]. A recent study suggested that NCX was causally linked to the spatial localization of JP-2 and organization of t-tubules in pressure-overloaded hearts [56], possibly due to abnormal JP-2 proteolysis through Ca-mediated calpain activation as previously described [57,58]. Whether the loss of TATs is a concomitant phenomenon of cellular remodeling or a direct consequence from the intracellular Ca elevation due to the absence of NCX in the KO cells remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…NCX1 is a crucial player in Ca 2+ homeostasis in cardiomyocytes [24]. Recent evidence from atrial-specific NCX1 knockout model [40] and cardiac-specific inducible NCX1 overexpression mice [41] suggest that NCX1 may mechanistically contribute to the proper spatial localization of JP2 and maintenance of T-tubule organization. This may represent an additional mechanism for the dysregulated E-C coupling and T-tubule remodeling in MG53-KO mice under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…JP2 is another membrane‐binding protein that physically connects the T‐tubule membrane with the SR membrane . The spatial distributions of LTCC and JP2 are consistent with the invaginations of the T‐tubule membrane . The loss and disorganization of T‐tubules is now understood to be an important cellular‐level contributor to HF, and the plasticity of this system may also be harnessed for therapy .…”
Section: Cardiac T‐tubule Microanatomy and Functionmentioning
confidence: 79%
“…Nevertheless, JP2 seems to be more important for controlling T‐tubule orientation and localization of nonjunctional RyRs rather than controlling T‐tubule density in cardiac muscle . It has been reported that T‐tubule disorganization is associated with a significant decrease in JP‐2 expression . However, knowledge of the molecular mechanisms of the downregulation of those proteins in failing hearts and the interaction between them are still unknown.…”
Section: Effect Of Bin1 On Cardiac Contractionmentioning
confidence: 99%
See 1 more Smart Citation